Berbagai Pendekatan Dan Usaha Untuk Mengurangi Occupational Fraud - Yulianto (LPPM POLITEKNIK LP3I BANDUNG, 2020)
Fraud is defined by Association of Certified Fraud Examiners (ACFE) as: “The use of one’s occupation for personal enrichment through the deliberate misuse or misapplication of the employing organization’s resources or assets. Occupation fraud and abuse is a widespread problem affects every organization. Survey participants estimated that the typical organization loses 5% of its revenues to fraud each year. Fraud harms everyone in the organization. Perpetrators committed fraud are influenced by three elements : motivation, opportunity, and rationalization. Three elements are called fraud triangle. Motives can be separated into four major categories such as psychotic, economic, egocentric, and ideological. Most of occupational frauds are committed for economic reasons, and are often attributable to alcoholism, drug abuse, gambling, and high living. Loose or lax controls and a work environment that does not value honesty provide the opportunity. When motives are coupled with such opportunities and rationalization, the potential for fraud is increased. The negative effects of fraud should be decreased through prevention and detection strategies. Fraud prevention means creating a work environment that values honesty. Senior managers who role-model truth and fairness in their daily interactions with their peers and subordinates can create such an environment. Prevention also means regularly monitored and enforced internal controls. Therefore, prevention strategies include tight controls, anti-fraud controls, ethical codes, fair treatment, awareness training, applicant screening, and honest role models. Detection strategies include monitoring variance reporting systems, internal audit, external audit, compliance audit, management review, account reconciliation.